Colltction of practical fnd test tasks for Information and Communication Technologies - Иксекбаева, Ж.С.; Хажгалиева, Г.Х.; Касымова, А.Х. (M.Utemisov West Kazakhstan State University, 2018)
This project explores the importance of cybersecurity in the modern digital world. It highlights the common online threats such as viruses, phishing, and malware, and provides practical tips for safe internet use. The project aims to raise awareness among students about protecting personal data and using digital technologies responsibly. By learning the basics of cybersecurity, users can avoid common risks and build a safer online environment.
Иксекбаева, Ж.С., Хажгалиева, Г.Х., Касымова А.Х. Colltction of practical fnd test tasks for Information and Communication Technologies. - Uralsk : M.Utemisov West Kazakhstan State University, 2023. - 192
Keywords: Digital literacy; Phishing; Cybersecurity; Internet safety; Malware; Antivirus; Password protection